Imantatänwa. The territorial fragmentation of the Aymara and Pastos, a form of geographic «genocide» and the right to their pre-existence Yaneth Katia Apaza Huanca - Apaza Huanca, Yaneth Katia (EUNOMÍA. Revista en Cultura de la Legalidad, 2025)
The fragmentation of ancestral territories between two or more countries of so-called indigenous identities, indigenous peoples, is a form of geographic ’genocide’ (Lemkin, 1945, 1946). It leads to their gradual death as an identity and culture because it causes the destructuring of their social, political, economic and population organization. In addition, it leads them to a continuous assimilation and internal colonialism within the States; this is the case of the Aymaras, fragmented between Argentina, Bolivia, Peru and Chile, and the Pastos, between the borders of Colombia and Ecuador. Thus, this article aimed to seek a legal alternative to this historical-structural problem. The method of study was the intrinsic analysis of collective cases (Aymaras and Pastos). It was concluded that to solve the territorial fragmentation of these and other identities, it is necessary to recognize their preexistence as a principle of life in international regulations, a crucial step that the audience can contribute to.